2013
DOI: 10.1021/nl403849g
|View full text |Cite
|
Sign up to set email alerts
|

Nanopore Integrated Nanogaps for DNA Detection

Abstract: A high-throughput fabrication of sub-10 nm nanogap electrodes combined with solid-state nanopores is described. These devices should allow concomitant tunneling and ionic current detection of translocating DNA molecules. We report the optimal fabrication parameters in terms of dose, resist thickness, and gap shape that allow easy reproduction of the fabrication process at wafer scale. The device noise and current voltage characterizations performed and the influence of the nanoelectrodes on the ionic current n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 27 publications
0
49
0
Order By: Relevance
“…EBL resist thickness, thickness of electrode metallic film) and very high reproducibility was obtained. Eighty‐five percent ( n = 72) of chips had nanogap thinner than 10 nm . Ivanov et al.…”
Section: Advanced Detection Methodsmentioning
confidence: 98%
“…EBL resist thickness, thickness of electrode metallic film) and very high reproducibility was obtained. Eighty‐five percent ( n = 72) of chips had nanogap thinner than 10 nm . Ivanov et al.…”
Section: Advanced Detection Methodsmentioning
confidence: 98%
“…Tremendous efforts have been undertaken to realize applications of the tunneling current approach for practical uses by incorporating nanopore technologies to the quantum mechanical approach, which enables the active drawing of single-polynucleotides in the gap by means of an electrophoretic control of the translocation dynamics [11,12,13,14,15]. In contrast to the progress, however, little efforts have been made to evaluate and enhance the temporal resolution of the tunneling current measurements, which is an important issue in respect to the nanopore sequencing wherein the constituent nucleobase molecules in DNA move through the electrode gap swiftly within microseconds [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The longlasting problem of DNA conductance (Livshits et al, 2014) has been the subject of discussion, since some experiments demonstrated that DNA can carry electric current (Fanget et al, 2014), while others showed no such conductance in DNA (Porath et al, 2004). The longlasting problem of DNA conductance (Livshits et al, 2014) has been the subject of discussion, since some experiments demonstrated that DNA can carry electric current (Fanget et al, 2014), while others showed no such conductance in DNA (Porath et al, 2004).…”
Section: Introductionmentioning
confidence: 99%